9. PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG PT.KARYA LESTARI - Mursalin, Muchlis; Maman, Maman (Sekolah Tinggi Teknologi 10 Nopember, 2018)
The developing of Information System has been progress rapidly, the case being by a lot of thing, and the various data have to process, serving in  the information. PT. Karya Lestari is a daily  goods company, as such , foods, drinkings, books, and drugs. The stock handling  is not easy to control, while still  manual using method's. So that reports need  a much time to do it.  The system is Information System of PT. Karya Lestari's  goods readystock . The aim of written reports scrip  is a term of graduation in Sekolah Tinggi Tekhnologi 10 Nopember. The method of using readystock information system of PT.Karya Lestari , there are several method, one of them observation,interview, and literlacy study. The hardware using is one unit computer, by RAM 2 GB Minimum, mouse, keybord, and one unit printer cartridge . The software using window 7, operating system, server SQL aplication, and microsoft Visual Basic, NET 2008 Studio. the applicable readystock information system of PT. Karya Lestari can be easily cotrolling of readystock reports.